Research on obtaining method of rotor moment of inertia of synchronous generator set suitable for different rated speed. (September 2020) - Wen, Libin
Abstract: Aiming at the problem that the moment of inertia of the rotor of the generator set is different from that of the generator set under different load rejection, according to the energy conversion characteristics of the generator set during the rotor rotation, the energy conversion balance equation of the rotor rotation process is put forward, which is applied to the load rejection process of the generator set under different load and calculated and analyzed, and the accurate moment of inertia of the rotor of the generator set is obtained, this method improves the accuracy of kinetic energy of generator, which is one of the parameters of generator model in power grid stability analysis.